Assessment of glycaemic control among self-reported cases of diabetes: an observation of a PPP model project - Prajapati, Jagruti; Oza, Jaydip; Patel, B. B.; Avashia, Sunil R. (International Journal Of Community Medicine And Public Health, 2018)
Background: Sociodemographic determinants of diabetes such as age, sex and socioeconomic status play a major role in diabetes outcome. It was necessary to design a research project to address this. The aim of this study is to determine the prevalence of diabetes and its sociodemographic factors such as age, gender, residential area, economic status and a level of education in the project districts. Methods: The cross sectional study was carried out in the project districts named Ahmedabad, Dahod and Valsad. Urban, rural and tribal population are above 30 years of age from different districts were covered to collect data on socio economic back ground and status of diabetes. Random blood sugar was measured by glucometer and glycosylated haemoglobin (HbA1c) by the HbA1c analyzer. Results: Proportion of male and female participants were near to equal. Percentage of self reported cases of diabetes (including controlled and uncontrolled) was 14.07% in urban areas while it was 5.24% in rural areas. Pre diabetes detection rate was more in rural area. During screening 11.83% of pre diabetes cases were identified. Difference between controlled and uncontrolled diabetes among illiterate and literate groups was statistically not significant. Conclusions: This preliminary observational study included more than 51000 participants visiting primary and community health centres from three districts of Gujarat. The public private partnership model helped in systematic approach towards screening and data collection. The study reported prediabetes cases higher than global prevalence. More controlled studies are required to define the mandatory screening protocol in resource constrained settings.